TRENDS IN THE MICROBIOLOGICAL SPECTRUM AND ANTIMICROBIAL RESISTANCE AMONG ICU PATIENTS DIAGNOSED WITH BACTEREMIA – A RETROSPECTIVE STUDY - goyal, aditi; gupta, sarvatman; bhumbla, upasana; kaur, kiranjeet (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this study were to determine the trends of microorganisms and their antimicrobial resistance pattern among ICU patients diagnosed with bacteremia. Methods: This retrospective study was conducted in the microbiology laboratory at a tertiary care teaching hospital from August 2021 to July 2022. A total of 2492 blood culture samples were collected from hospital ICUs from the patient with suspected septicemia. All samples were processed using the automated blood culture system BACT/ALERT 3D/60 for the recovery of pathogenic microorganisms, and antimicrobial susceptibility testing was performed using the automated VITEK 2 Compact system. A Chi-square test was done to assess the statistical significance of our results. Results: Out of 2492 blood culture samples, 296 (11.87%) were identified as culture positive, in which 252 (85.13%) were Gram-negative isolates, 38 (12.83%) were Gram-positive isolates, and 06 (2.02%) were other organisms (contaminants). Gram-negative isolates showed maximum sensitivity to colistin 205 (81.40%), and Gram-positive isolates showed maximum sensitivity to vancomycin 35 (92.10%). Conclusion: Early blood culture results could provide the basis for the appropriate use of antibiotics that can improve clinical prognosis and help in reducing mortality.